أثر ممارسة أنماط القيادة الإدارية على الالتزام التنظيمي للعاملين من وجهة نظرهم: دراسة ميدانية بالمؤسسة العمومية الاستشفائية "براهمية مسعود" ببوشقوف - يوسفي, راضية; بخاخشة, موسى (جامعة الوادي - University of Eloued, 2018)
The aim of this study is to identify the level of practice leadership management styles and their impact on the organizational commitment of the employees of the hospital public institution - Brahmia Messaoud- in Bouchegouf wilaya of Guelma, and to achieve this goal, was developed a questionnaire consisting of (34) paragraphs distributed on two axes (leadership management styles and organizational commitment) and used as a principal tool for collecting primary data. And through the field survey and the application of the tool to the members of the sample and analysis using SPSS program (V 24) study concluded a set of results: the democratic style is prevailing and its application was medium with an average of (3.46) followed by a less autocratic and finally the free style by a low-grade, the overall level of leadership management is medium, the normative commitment is the commitment shown by the workers in the first rank with an average of (3.67) followed by effective commitment and continuous, and all dimensions are medium, the general level of organizational commitment is medium, there is a statistically significant effect of the democratic style on the organizational commitment of the employees, while there is no impact of autocratic and free style.
The impact of leadership management styls on the organizational commitment of employees from their point of view - A fieled study in the hospital public institution "Brahmia Messaoud" in Bouchegouf -
مقال
Keywords: القيادة الإدارية؛ أنمطا القيادة الإدارية؛ الالتزام التنظيمي؛ أبعاد الالتزام التنظيمي؛ المؤسسة العمومية الاستشفائية "براهمية مسعود" ببوشقوف.; Leadership management, leadership management styles, organizational commitment, dimensions of organizational commitment